Activity of Ceftazidime–Avibactam Against Respiratory Isolates of Enterobacteriaceae and Pseudomonas aeruginosa Collected in Asia/Pacific as part of the INFORM Global Surveillance Program, 2014–2016. (4th October 2017) - Kazmierczak, Krystyna; Wise, Mark; Stone, Gregory G; Sahm, Dan
Abstract: Background: Avibactam (AVI) is a non-β-lactam β-lactamase inhibitor that restores the in vitro activity of ceftazidime (CAZ) against class A, class C, and some class D β-lactamases, including extended-spectrum β-lactamases, serine carbapenemases, and the chromosomal AmpC of Pseudomonas aeruginosa ( Pae ). This study evaluated the in vitro activity of CAZ-AVI and comparators against Enterobacteriaceae ( Eba ) and Pae collected from patients with lower respiratory tract infections (LRTI) in Asia/Pacific in 2014–2016 as part of the INFORM surveillance program. Methods: Non-duplicate isolates from patients with LRTI were collected from 28 medical centers in Australia, Hong Kong, Japan, Malaysia, Philippines, South Korea, Taiwan, and Thailand. Susceptibility (S) testing was performed by broth microdilution and interpreted using FDA breakpoints for CAZ-AVI and CLSI breakpoints for comparators. AVI was tested at a fixed concentration of 4 µg/mL with doubling dilutions of CAZ. Multidrug resistance (MDR) phenotype was defined as resistant by CLSI breakpoints to sentinel agents from ≥3 drug classes. Results: CAZ-AVI showed potent in vitro activity against the overall population of Eba (MIC90, 0.5 µg/mL; 98.0% S) and against ceftazidime-nonsusceptible (CAZ-NS), colistin-resistant (CST-R), and MDR isolates, with >91% of these resistant subsets testing as susceptible (MIC ≤8 µg/mL). Reduced activity against meropenem-nonsusceptible (MEM-NS) Eba was attributable to the presence of class B metallo-β-lactamases (MBL); 95.7% of MEM-NS, MBL-negative isolates were susceptible to CAZ-AVI. CAZ-AVI also showed good activity against most Pae isolates (MIC90, 8 µg/mL; 92.5% S), as well as CST-R isolates (MIC90, 8 µg/mL; 100% S). Activity of CAZ-AVI was reduced against CAZ-NS, MEM-NS, MEM-NS MBL-negative, and MDR Pae subsets (46.9–82.3% S) but exceeded the activity of CAZ and MEM. Conclusion: CAZ-AVI is a potential therapeutic option for treating respiratory infections in the Asia/Pacific region caused by Eba and Pae isolates resistant to commonly used and last-in-line agents. Disclosures: G. G. Stone, Pfizer: Employee,  Salary AstraZeneca: Shareholder, Capital Gains